Strategi Downward Communication Pimpinan dalam Meningkatkan Efektivitas Kerja Karyawan di PT. Pelabuhan Indonesia I - Hefa Yolanda; Yan Hendra; Armansyah Matondang (Universitas Medan Area, 2020)
According to the observations by researchers that communication from business leaders to their subordinates still shows the boundary between leaders and subordinates. This phenomenon is the reason in this study. Information received by employees received in advance by a senior assistant manager of business development, The information received by employees is also not intact, because in this field of business development if there is a message to be delivered by the leader then the first person receiving the message is a senior assistant manager. The purpose of this study is to find out how the leadership’s downward communication strategy in improving employee work effectiveness at PT. Pelabuhan Indonesia I (PERSERO), as well as any factors that become obstacles to the downward communication strategy of business development leaders. This study used situational theory on this reaserch. The researcher selected the business manager’s senior manager as a key informant, and five additional informants to strengthen the validity of a study. The results of this research process, the researchers found that with the instruction of task, openness, trust, information, feedback carried out by business leaders to their employees had been well implemented.